One-dimensional coordination polymers constructed from binuclear 3d–4f nodes and isonicotinato spacer. Issue 25 (24th May 2016) - Patrascu, Andrei A.; Calancea, Sergiu; Cassaro, Rafael A. Allão; Soriano, Stéphane; Madalan, Augustin M.; Maxim, Catalin; Novak, Miguel A.; Vaz, Maria G. F.; Andruh, Marius
Abstract : Coordination polymers were assembled from M II Ln III nodes, connected by isonicotinato spacer. Slow relaxation of the magnetization for the Ni II Dy III nodes was observed. Abstract : Three new 1-D coordination polymers, [Co(valpn)Gd(hfac)2 (IN)] n (1 ), [Ni(valpn)Gd(hfac)2 (IN)] n (2 ), and [Ni(valpn)Dy(hfac)2 (IN)] n (3 ), were constructed by connecting {M II (valpn)Ln III (hfac)2 } nodes through isonicotinato spacers (IN − ), with hexafluoroacetylacetonato being hfac and 1, 3-propanediylbis(2-iminomethylene-6-methoxy-phenol) (H2 valpn) being the Schiff base obtained from the condensation reaction between o-vanillin and 1, 3-diaminopropane. The synthetic approach relied on the substitution of the acetate ligands from the binuclear precursors [M II (CH3 OH)(valpn)Ln III (hfac)2 (CH3 COO)] with the isonicotinato ligand. The investigation of the magnetic properties of all compounds showed a ferromagnetic interaction attributed to the intranode exchange interaction between the 3d and 4f metal ions. For compound3, the AC magnetic measurements indicated a field-induced slow relaxation of the magnetization of the [Ni II Dy III ] nodes.